Formulasi dan Evaluasi Sediaan Sampo Ekstrak Lidah Buaya (Aloe vera L.) dengan Surfaktan Sodium Laureth Sulfate - Carissa Putri Aurellia Darmawan (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study aims to formulate and evaluate an aloe vera (Aloe vera L.) extract shampoo preparation using Sodium Laureth Sulfate as the main surfactant. Aloe vera was used as a natural active ingredient that functions to moisturize and nourish the hair. The shampoo was prepared by mixing the ingredients according to their solubility order until a homogeneous preparation was obtained. The evaluation included organoleptic tests, pH, viscosity, foam height, and foam stability. The results showed that the preparation had a homogeneous liquid form, white in color, and without a rancid odor, with a pH of 7.23, which is still safe for the scalp. The foam height reached 11 cm and remained stable after four minutes, while the viscosity of 145.3 cPs indicated a slightly thin but acceptable consistency. Overall, the aloe vera extract shampoo formulation produced a stable, safe, and physically high-quality preparation.